TREATMENT OF DOG CARIES-PULPIT DISEASES - Kyrychko, B. P. (Scientific Progress & Innovations, 2020)
At present the field of animals’ endodontic treatment is insufficiently covered in Ukrainian scientific lit- erature, but occupies an important place in dental treatment. Therefore, our aim was to collect reports from foreign and domestic veterinary publications concerning pulp involvements in dogs. Many of these materials were taken from humane medicine, namely humane dentistry. Endodontic treatment is required if the pulp is inflamed and pathogenic or conditional pathogenic micro-flora entered the root canal. Most often, pulpitis is caused by mechanical injury to the teeth. A fractured tooth root causes acute traumatic pulpitis. Splitting of the tooth crown can lead to chronic fibrous pulpitis. The treatment of the root canal consists of two main stages: instrumental treatment and root canal filling. Instrumental treatment consists of cleaning up the root canal from the pulp remnants or its decay, softened infected dentine, foreign particles. Practicing veterinary dentists most often use the “step back” technique for root canal treatment as it involves the using of hand tools only. This technique has three stages and consists of cleaning up and expanding the tooth root canal. At pulpitis or periodontitis, tissue decay products and microbial toxins are accumulated in the root canal and apical periodontium, which requires high quality medical treatment of the canals, which is carried out both simultaneously with instrumental treatment and after its conducting. It is necessary to wash the canals for at least 15–20 minutes per canal using 3 % sodium hypochlorite and 3% hydrogen peroxide solution al- ternately for 3 minutes each. The final stage in tooth endodontic treatment is inserting a permanent filling. For this purpose, different filling materials are used, which also came from humane dentistry. It is best to use light polymerization composites, as they have approximately the same expansion coefficients at tempera- ture changes and the closest mechanical strength, which is almost the same as healthy tooth enamel.